Deashing Pada Batubara Menggunakan KOH dan HNO3 Sebagai Leaching Agent - Hendly Syahputra Pratama; Fadhilah Fadhilah (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. The negative effects of the high ash content of coal results in cement factories, air pollution and other damaging effects. In addition, it is also inefficient if it is used for carbonization, combustion, gasification, and liquefaction purposes. Therefore we need a way to reduce the ash content of coal. The process of reducing coal ash content is known as deashing. The most effective deashing method is chemical washing of coal using alkaline and acid solutions, also known as the leaching method. KOH and HNO3 are the solvents most commonly used as leaching agents in the deashing process. The coal used in this study is Seam C coal from the CV. Tahiti Coal Sawahlunto. Seam C coal has an ash content of 16.5%. Coal samples were leached using KOH and HNO3 with variations of 5%, 10%, 20%, and 30% for KOH while the concentration of HNO3 was 10%. After leaching the samples were analyzed using the LECO TGA701. The optimum conditions were obtained at concentrations of KOH and HNO3 of 30% and 10%.Keywords: deashing, coal, ash, potassium hydroxide, nitric acid